PENERAPAN MODEL PEMBELAJARAN ACCELERATED LEARNING TIPE MASTER UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF FISIKA DI SMK LABOR BINAAN FKIP UR PEKANBARU - Tranminingsih, Utami; Islami, Nur; Syahril, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aimed to describe the results of cognitive learning physics outcome through the implementation of accelerated learning MASTER type model in SMK Labor Binaan FKIP UR Pekanbaru. The type of research is pre experimental, with a comparison group design intact. The subjek of this research is XI TKJ class with 22 students which used implementation with accelerated learning MASTER type learning model, and XI RPL class with 26 students that used conventional learning classes. The data in this study were analyzed descriptively. Based on the result of cognitive learning of students in the class implementation of accelerated learning MASTER type are in the very good category with persentse 85.22% whereas, in the conventional classroom learning cognitive the category good with the percentage 76.36%. It can be concluded that science teaching physics with accelerated learning MASTER type learning model can improve cognitive achievement of students in the temperature and heat material in SMK Labor Binaan FKIP UR Pekanbaru.Keywords: Learning Outcomes, Accelerated Learning MASTER Type, Temperature and Heat